Pediatric Abdominal Infection and Inflammation: Choosing the Appropriate Diagnostic Imaging Study - Chapman, Teresa; Khalatbari, Hedieh (Journal of Pediatric Infectious Diseases, 2017)
Diagnostic imaging for the evaluation of abdominal infection or inflammation in the child may be required to identify a source of infection, guide percutaneous biopsy for a tissue diagnosis, or determine length of medical therapy. Several anatomic and functional imaging techniques are available, and determining which of these examinations is appropriate can be confusing. Criteria published by the American College of Radiology serve to guide clinicians and radiologists in making these decisions appropriately. In this review, current imaging recommendations relevant to abdominal infection in the child are discussed.
Keywords: pediatric; diagnostic imaging; abdominal; infection; inflammation